Comparative Study of Flavonoid Profiles, Antioxidant, and Antiproliferative Activities in Hot-Air and Vacuum Drying of Different Parts of Pitaya (Hylocereus undatus Britt) Flowers - Caifeng Shi; Huaqian Long; Jia Hu; Xinbo Guo (MDPI AG, 2024)
Pitaya flower, a medicinal and edible plant commonly used in tropical and subtropical regions, was the focus of this study, which compared the effects of hot-air drying (HAD) and vacuum drying (VD) on phytochemical profiles and biological activities of its four parts: calyx, petals, stamens, and pistils. Both drying methods significantly increased the total phenolic content (TPC) of pitaya flowers, with values ranging from 1.86 to 3.24 times higher than those of fresh samples. Twelve flavonoid compounds were identified in pitaya flowers, with the glycoside derivatives of three flavonols (kaempferol, isorhamnetin, and quercetin) being the most abundant. VD resulted in 1.15 times higher total flavonoid glycoside content than HAD, whereas in petals, HAD yielded a total flavonoid glycoside content 1.21 times higher than VD. Both HAD and VD effectively increased the antioxidant capacities of pitaya flowers, though the difference between the two methods was not significant. Additionally, both drying methods enhanced the antiproliferative activity of pitaya flowers, with HAD showing a more significant effect than VD. The present study emphasized the efficacy of drying methods for enhancing flavonoids in pitaya flowers and provided insights for functional products' innovation with different parts of pitaya flowers.